Study the Factors Effecting on Welding Joint of Dissimilar Metals - Khuder, Abdul wahab H.; Ebraheam, Esam J. (Al-Khwarizmi Engineering Journal, 2019)
The aim of this work is to study the factors that affect the welding joint of dissimilar metals. Austenitic stainless steel-type AISI (316L) with a thickness of (2mm) was welded to carbon steel (1mm) using an MIG spot welding. The filler metal is a welding wire of the type E80S-G (according to AWS) is used with (1.2mm) diameter and CO2 is used as shielding gas with flow rate (7L/min) for all times was used in this work. The results indicate that the increase of the welding current tends to increase the size of spot weld, and also increases the sheer force. Whereas the sheer force increased inversely with the time of welding. Furthermore, the results indicate that increasing the current and time of welding increases the diameter of weld zone, and decreases the sheer force.